Isolation of Stable Mutants of Candida guilliermondii Producing One Type of ADH - Retno Indrati; Yoshiyuka Ohta (Indonesian Food and Nutrition Progress, 1994)
Mutants of Candida guilliermondii partially deficient in alcohol dehydrogenase (ADH) were isolated using allyl alcohol as a selective agent. On glucose medium containing allyl alcohol produced mutants deficient in ADH1, while mutants free of ADH2 were isolated on ethanol medium containing allyl alcohol. An addition of 1% of yeast extract to the isolation medium resulted in a stability of the mutants againts a high concentration of allyl alcohol. On this medium the cells resistant up to 80 mM of allyl alcohol compared to those with a resistance of 10 mM allyl alcohol on basal salt medium without addition of yeast extract. Furthermore, this resistance to allyl alcohol seems to be related to a stability of the mutants to produce only one type of ADH for a long incubation period (more than 2 years). Cells which were resistant only up to 10 mM of allyl alcohol started to produce two kind of ADHs after six months of incubation. However, this resistance to a high allyl alcohol resulted in a decrease of specific activity of ADHs. Mutant ADH1s had activities only 23 – 50%, where as mutant ADH2s had only 1 – 3% of the parent strain activity.